How to Apply of Design Application as a Medium for Learning Arabic - Amelia, Amelia; Amri , Yazeed; Ali, Juneed (Journal International of Lingua and Technology, 2022)
In this digital era, innovative and effective learning approaches are needed to improve students' understanding in learning Arabic. Therefore, this study aims to explore the potential of applying design applications as Arabic learning media. The main objective of this study is to evaluate the effectiveness and efficacy of applying design applications as Arabic learning media in improving students' understanding of the subject matter. In addition, this study also aims to identify the advantages and disadvantages of design apps in the context of Arabic language learning. The research method used in this study is the experimental method. The research participants will be divided into two groups: a group that uses design apps as learning media and a control group that uses conventional learning methods. Data will be collected through material comprehension tests, observations, and questionnaires to evaluate the effectiveness of design apps as learning media. The results show that the application of design apps as Arabic learning media significantly improves students' understanding of the subject matter. The group that used the design app showed a greater improvement in the understanding of Arabic concepts compared to the control group that used conventional learning methods. In addition, students also showed a higher level of motivation in learning Arabic through design apps. The research method used in this study is the experimental method. The research participants will be divided into two groups: a group that uses design apps as learning media and a control group that uses conventional learning methods. Data will be collected through material comprehension tests, observations, and questionnaires to evaluate the effectiveness of design apps as learning media. The results show that the application of design apps as Arabic learning media significantly improves students' understanding of the subject matter. The group that used the design app showed a greater improvement in the understanding of Arabic concepts compared to the control group that used conventional learning methods. In addition, students also showed a higher level of motivation in learning Arabic through design apps.